2006
DOI: 10.1093/glycob/cwl036
|View full text |Cite
|
Sign up to set email alerts
|

Flagellasialin: a novel sulfated  2,9-linked polysialic acid glycoprotein of sea urchin sperm flagella

Abstract: A novel alpha2,9-linked polysialic acid (polySia)-containing glycoprotein of sea urchin sperm flagella was identified and named "flagellasialin." Flagellasialin from Hemicentrotus pulcherrimus shows a diverse relative molecular mass on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of 40-80 kDa. Flagellasialin is a 96-amino acid, threonine-rich, heavily O-glycosylated (80-90% by weight) glycoprotein with a single transmembrane segment at its C-terminus and no apparent cytosolic domain. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 50 publications
6
58
0
Order By: Relevance
“…They participate in the recognition and interaction events that are essential for the growth, development and immunological reaction of these organisms (Nasirikenari et al 2006;Nacher et al 2010). Occasionally, sialic acids may be linked to each other to form polymeric structure, as in the capsules of some pathogenic bacteria and in few animal structures (Miyata et al 2006). Sialic acid-rich glycoconjugates are found in the zona pellucid of mammalian eggs and also in the jelly coat and vitelline layer overlying sea urchins eggs (Vilela-Silva et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They participate in the recognition and interaction events that are essential for the growth, development and immunological reaction of these organisms (Nasirikenari et al 2006;Nacher et al 2010). Occasionally, sialic acids may be linked to each other to form polymeric structure, as in the capsules of some pathogenic bacteria and in few animal structures (Miyata et al 2006). Sialic acid-rich glycoconjugates are found in the zona pellucid of mammalian eggs and also in the jelly coat and vitelline layer overlying sea urchins eggs (Vilela-Silva et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was highly sulfated but differed from a similar molecule found in the egg jelly due to the occurrence of Neu5Ac instead of Neu5Glc and also due to very low proportion of other constituent sugars (Table 1). The sialic acid-rich polysaccharide from the sperm head had similarity with another glycoconjugate, named flagellasialin, which also contained Neu5Ac (Miyata et al 2006(Miyata et al , 2011. Studies on whether the sialic acid-rich molecule found in the sperm head interacted with the sulfated fucan from the egg jelly followed the analogy of the interaction of sulfated polysaccharides that regulated sponge cell-cell adhesion (Vilanova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to vertebrates, however, also ␣2,9-and ␣2,5-O-glycolyl-linked polySia exist in addition to the ␣2,8-linked form. Kitajima and co-workers (31) show that polySia mediates important functions of sea urchin sperm. For instance, ␣2,9-linked polySia is suggested to influence the motility of sea urchin sperm, and ␣2,5-O-glycolyllinked polySia is discussed to potentiate the acrosome reaction (30).…”
Section: Fertilization In Animals Is a Complex Sequence Of Several Bimentioning
confidence: 99%